2016
DOI: 10.1016/j.entcom.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Entertaining the similarities and distinctions between serious games and virtual heritage projects

Abstract: This article describes the primary ways in which intelligent agents have been employed in virtual heritage projects and explains how the special requirements of virtual heritage environments necessitate the development of cultural agents. How do we distinguish between social agents and cultural agents? Can cultural agents meet these specific heritage objectives?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…For instance, they can have an information overload effect on tourists, who may feel overwhelmed with the amount or pace of information, or find some information irrelevant (Kounavis et al, 2012). Simulating historical events in serious-games can raise ethical concerns regarding accurateness and violence, but virtual heritage projects can include some of the serious games-style goals and elements, thus entertaining visitors (Champion, 2016). In spite of these issues, "(...) AR has the potential to enhance tourists' experiences and make them exceptional" (Yovcheva, Buhalis, Gatzidis, & van Elzakker, 2014).…”
Section: Enhancing Cultural Heritage With Armentioning
confidence: 99%
“…For instance, they can have an information overload effect on tourists, who may feel overwhelmed with the amount or pace of information, or find some information irrelevant (Kounavis et al, 2012). Simulating historical events in serious-games can raise ethical concerns regarding accurateness and violence, but virtual heritage projects can include some of the serious games-style goals and elements, thus entertaining visitors (Champion, 2016). In spite of these issues, "(...) AR has the potential to enhance tourists' experiences and make them exceptional" (Yovcheva, Buhalis, Gatzidis, & van Elzakker, 2014).…”
Section: Enhancing Cultural Heritage With Armentioning
confidence: 99%
“…Furthermore, Christopoulou & Xinogalos [29] found that, of the different game engines used in serious games, Unity and Unreal Engine 4 were the most common, both of which enable the generation of high-fidelity, photorealistic 3D games. However, there are many challenges associated with the use of such 3D graphics technology, including the acquisition and preservation of accurate 3D models [30], the presentation of difficult information such as violence or uncertainty within the source material [31], and the cost for both the user, who requires modern computing hardware to run the applications, and the developer who must design and create the environments. It is widely acknowledged that modern state-of-the-art video games can be extremely expensive to make, and the design, artwork, modelling, texturing, animation, and testing of elaborate 3D environments are just some of the factors that contribute to this.…”
Section: Serious Games and Virtual Environments For Heritagementioning
confidence: 99%
“…In the current study we have not investigated using different visual styles, although this presents an interesting avenue for further research. Constrained environments may offer innovative methods to overcome some of the challenges of representation faced by SGsH, such as violence within the source material or uncertainty in the current state of historical knowledge [31], compounded by the expectation of younger participants that everything they see in the virtual environment is presented as it truly was [26]. These could be tackled using the fact that not everything is shown in exhaustive detail in a constrained environment; information can be obscured or only suggested to the user.…”
Section: Constrained Environment Presentationmentioning
confidence: 99%
“…On the other hand, games also used for not only entertainment but for more critical tasks which are then associated to the term serious games [54], [59]. Among critical tasks which have been developed using serious games are in virtual heritage projects [51], attention assessment for cerebral palsy [55], in tourism [56], in retraining cognition for elderly [57], in educating domestic energy consumption [58], and nutrition education for children [61]. There is also an attempt to apply game aesthetics using machine learning [53].…”
Section: Introductionmentioning
confidence: 99%